Growth, Condition, and Trophic Relations of Stocked Trout in Southern Appalachian Mountain Streams. Issue 4 (18th June 2019) - Fischer, Jesse R.; Kwak, Thomas J.; Flowers, H. Jared; Cope, W. Gregory; Rash, Jacob M.; Besler, Douglas A.
Abstract: Stream trout fisheries are among the most popular and valuable in the United States, but many are dependent on hatcheries to sustain fishing and harvest. Thus, understanding the ecology of hatchery‐reared trout stocked in natural environments is fundamental to management. We evaluated the growth, condition, and trophic relations of Brook Trout Salvelinus fontinalis, Brown Trout Salmo trutta, and Rainbow Trout Oncorhynchus mykiss that were stocked in southern Appalachian Mountain streams in western North Carolina. Stocked and wild (naturalized) trout were sampled over time (monthly; September 2012–June 2013) to compare condition and diet composition and to evaluate temporal dynamics of trophic position with stable isotope analysis. Relative weights ( W r ) of stocked trout were inversely associated with their stream residence time but were consistently higher than those of wild trout. Weight loss of harvested stocked trout was similar among species and sizes, but fish stocked earlier lost more weight. Overall, 40% of 141 stomachs from stocked trout were empty compared to 15% of wild trout stomachs ( N  =   26). We identified a much higher rate of piscivory in wild trout (18 times that of stocked trout), and wild trout were 4.3 times more likely to consume gastropods relative to stocked trout. Hatchery‐reared trout were isotopically similar to co‐occurring wild fish for both δ 13 C and δ 15 N values but were less variable than wild trout. Differences in sulfur isotope ratios (δ 34 S) between wild and hatchery‐reared trout indicated that the diets of wild fish were enriched in δ 34 S relative to the diets of hatchery‐reared fish. Although hatchery‐reared trout consumed prey items similar to those of wild fish, differences in consumption or behavior (e.g., reduced feeding) may have resulted in lower condition and negative growth. These findings provide critical insight on the trophic dynamics of stocked trout and may assist in developing and enhancing stream trout fisheries.